Evaluation of the psychometric properties of the Greek version of the Active Life with Asthma (Gr-ALMA) review: a descriptive methodological study - Livadiotis, Chris; Lambrinou, Ekaterini; Raftopoulos, Vasilios; Middleton, Nicos (My University, 2019)
BACKGROUND: Regular asthma reviews are recommended by international guidelines to improve the quality of life of asthma patients. To facilitate these reviews in primary care practice, there is a need for structured asthma review tools. AIM: The aim of this study was to assess the metric properties of the Greek-translated version of the Active Life with Asthma (ALMA) review. METHODS: A convenience sample of 156 asthmatic patients from three public hospitals participated in this methodological study with a descriptive cross-sectional correlation design. Participants responded to the 19-item ALMA questionnaire and provided socio-demographic and clinical information. The construct validity of the tool was explored in exploratory factor analysis and the internal consistency of scale and sub-scales was estimated using Cronbach's α. Convergence validity was assessed using the Asthma Control Questionnaire (ACQ), a commonly used asthma control measure, and concurrent criterion validity was assessed using the MiniAQoL, an asthma-specific quality of life questionnaire. Known-group validity was assessed based on observed differences in terms of frequency of hospitalizations or emergency visits in the past year. RESULTS: Amongst 156 participants, 95 (60.9%) were women and the median age was 50-65 years old. Exploratory factor analysis (KMO = 0.83 and Bartlett test < 0.001) with principal component extraction and orthogonal rotation revealed a clear structure of three factors with little cross-loading: physical, environmental and mental domains, as in the original study. Cronbach's alpha coefficient for internal consistency for the whole scale was 0.85, while for the sub-scales, these were: environmental a = 0.69, mental a = 0.76 and physical a = 0.85. Test-retest reliability based on the correlation between scores of 20 participants responding twice two weeks apart was r = 0.92. There was stong correlation in the expected direction between ALMA and ACQ (r = - 0.70) as well as miniAQoL (r = 0.71). Finally, there were statistically significant higher ALMA scores in participants who reported emergency visits and hospital admissions in the past year. CONCLUSION: In general, the ALMA showed good metric properties. It appears to be a reliable and valid tool which can be used as a measure for asthma control and self-management in clinical practice as well as future descriptive or intervention research studies.
Keywords: Asthma; Asthma control; Metric properties; Quality of life; Self-management